The Problem of Countering Violent Extremism inthe Information War - Viktor Petrovich Kirilenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
International extremism has become one of the most dangerous comprehensive security threats of the XXI century. The ideology of violent extremism is a genetic source of terrorism and poses a significant threat to global peace and security. Aggression of the extremist communities causes social consequences which severity is comparable to operations of a military nature. Prohibition under criminal law of extremism propaganda aimed at the protection of human rights, life and health of the people and is an integral element of the developed countries legal system.